Diagnostics of Piezoelectric Bending Actuators Subjected to Varying Operating Conditions - Aimiyekagbon, Osarenren Kennedy; Bender, Amelie; Hemsel, Tobias; Sextro, Walter (Electronics)
In applications of piezoelectric actuators and sensors, the dependability and particularly the reliability throughout their lifetime are vital to manufacturers and end-users and are enabled through condition-monitoring approaches. Existing approaches often utilize impedance measurements over a range of frequencies or velocity measurements and require additional equipment or sensors, such as a laser Doppler vibrometer. Furthermore, the non-negligible effects of varying operating conditions are often unconsidered. To minimize the need for additional sensors while maintaining the dependability of piezoelectric bending actuators irrespective of varying operating conditions, an online diagnostics approach is proposed. To this end, time- and frequency-domain features are extracted from monitored current signals to reflect hairline crack development in bending actuators. For validation of applicability, the presented analysis method was evaluated on piezoelectric bending actuators subjected to accelerated lifetime tests at varying voltage amplitudes and under external damping conditions. In the presence of a crack and due to a diminished stiffness, the resonance frequency decreases and the root-mean-square amplitude of the current signal simultaneously abruptly drops during the lifetime tests. Furthermore, the piezoelectric crack surfaces clapping is reflected in higher harmonics of the current signal. Thus, time-domain features and harmonics of the current signals are sufficient to diagnose hairline cracks in the actuators.
Keywords: piezoelectric transducer; self-sensing; fault detection; diagnostics; hairline crack; condition monitoring

Estimating States and Model Uncertainties Jointly by a Sparsity Promoting UKF - Götte, Ricarda-Samantha; Timmermann, Julia (12th IFAC Symposium on Nonlinear Control Systems (NOLCOS 2022))
State estimation when only a partial model of a considered system is available remains a major challenge in many engineering fields. This work proposes a joint, square-root unscented Kalman filter to estimate states and model uncertainties simultaneously by linear combinations of physics-motivated library functions. Using a sparsity promoting approach, a selection of those linear combinations is chosen and thus an interpretable model can be extracted. Results indicate a small estimation error compared to a traditional square-root unscented Kalman filter and exhibit the enhancement of physically meaningful models.
Keywords: joint estimation; unscented transform; Kalman filter; sparsity; data-driven; compressed sensing

Modellierung und experimentelle Charakterisierung der Wechselwirkung zwischen Ultraschallwandler und Flüssigkeit in kavitationsbasierten Prozessen - Bornmann, Peter
Ultraschall wird zur Effizienzsteigerung in verfahrenstechnischen Prozessen eingesetzt. Die Betriebsparamter der Ultraschallsysteme werden empirisch ermittelt, da derzeit keine systematische Analyse der Wechselwirkung zwischen Ultraschallwandler und Schallfeld sowie kein Verfahren zur Messung der Kavitationsaktivität ohne zusätzlichen Sensor existieren. Auf Basis einer experimentellen Analyse des betrachteten sonochemischen Reaktors wird ein Finite-Elemente-Modell aufgebaut, das die Wechselwirkung zwischen Schallfeld und Ultraschallwandler berücksichtigt. Die modellbasierte Analyse zeigt, dass wegen der akustischen Eigenschaften des Autoklavs nur direkt an der Sonotrode Kavitation entsteht. Die Wechselwirkung zwischen Ultraschallwandler und Schallfeld ermöglicht Aussagen über das Schallfeld und die Kavitationsaktivität auf Basis der Rückwirkung auf den Ultraschallwandler. Die lineare Schalldruckverteilung ermöglicht eine Prognose über die Verteilung von Kavitationszonen. Das beschriebene Modell liefert wertvolle Erkenntnisse für die Auslegung, Analyse und Skalierung sonochemischer Reaktoren. Auf Grund der rauen Prozessrandbedingungen ist die Applikation von Sensoren zur Überwachung der Kavitationsaktivität in vielen sonochemischen Prozessen nicht möglich. Zur prozessbegleitenden Messung der Kavitationsaktivität wird ein Verfahren entwickelt, das die Bewertung der Kavitationsaktivität durch Auswertung der Rückwirkung auf den Ultraschallwandler erlaubt. Das Messverfahren ermöglicht eine vorhersagbare und reproduzierbare Durchführung kavitationsbasierter Prozesse und stellt eine wichtige Erweiterung für bestehende und neue Ultraschallsysteme dar.
Keywords: Sonochemie; Akustische Kavitation; Kavitationsmessung; Kavitationsdetektion; FEM-Simulation Ultraschallwandler; Prozessüberwachung; FEM-Simulation Schallfeld; Self-Sensing; Piezoelektrische Ultraschallwandler; Ultraschallreinigung

Estimation of Remaining Useful Lifetime of Piezoelectric Transducers Based on Self-Sensing - Kimotho, James Kuria; Sextro, Walter; Hemsel, Tobias (IEEE Transactions on Reliability)
Piezoelectric transducers are used in a wide range of applications. Reliability of these transducers is an important aspect in their application. Prognostics, which involve continuous monitoring of the health of technical systems and using this information to estimate the current health state and consequently predict the remaining useful lifetime (RUL), can be used to increase the reliability, safety, and availability of the transducers. This is achieved by utilizing the health state and RUL predictions to adaptively control the usage of the components or to schedule appropriate maintenance without interrupting operation. In this work, a prognostic approach utilizing self-sensing, where electric signals of a piezoelectric transducer are used as the condition monitoring data, is proposed. The approach involves training machine learning algorithms to model the degradation of the transducers through a health index and the use of the learned model to estimate the health index of similar transducers. The current health index is then used to estimate RUL of test components. The feasibility of the approach is demonstrated using piezoelectric bimorphs and the results show that the method is accurate in predicting the health index and RUL.
Keywords: Estimation of Remaining Useful Lifetime of Piezoelectric Transducers Based on Self-Sensing

Kavitationsdetektion mittels Self-Sensing-Ultraschallwandler - Bornmann, Peter; Hemsel, Tobias; Sextro, Walter; Memoli, Gianluca; Hodnett, Mark; Zeqiri, Bajram (tm - Technisches Messen)
Eine Vielzahl von Prozessen in der Chemie und Verfahrenstechnik kann durch Ultraschall positiv beeinflusst werden. Oftmals ist ultraschallinduzierte Kavitation der Hauptwirkmechanismus für die positiven Effekte der Beschallung. Daher ist es notwendig die Kavitationsaktivität während des Prozesses zu quantifizieren um die Beschallung für den jeweiligen Prozess optimal gestalten und überwachen zu können. Eine Möglichkeit der prozessbegleitenden Kavitationsdetektion ist die Auswertung der akustischen Emissionen von oszillierenden und kollabierenden Kavitationsblasen mittels Drucksensoren in der Flüssigkeit. Raue Prozessrandbedingungen wie hohe Temperaturen oder aggressive Flüssigkeiten erschweren es jedoch geeignete Sensoren zu finden. Als Alternative wurde daher die Nutzbarkeit der Rückwirkung von Kavitationsereignissen auf das elektrische Eingansgssignal des Ultraschallwandlers zur Quantifizierung von Kavitation untersucht. Die experimentelle Analyse hat ergeben, dass das Einsetzen und in einigen Fällen auch die Art der Kavitation auf Basis der Rückwirkung auf das Stromsignal des Ultraschallwandlers bestimmt werden kann. Die Stärke der Kavitation war hingegen nicht aus den Stromsignalen abzuleiten.
Keywords: Kavitationsdetektion; Self-Sensing; So- nochemie; Ultraschallwandler

Request Driven Social Sensing - King, Thomas C.; Liu, Qingzhi; Polevoy, Gleb; de Weerdt, Mathijs; Dignum, Virginia; van Riemsdijk, M. Birna; Warnier, Martijn (Proceedings of the 2014 International Conference on Autonomous Agents and Multi-agent Systems)
Keywords: crowd-sensing; crowdsourcing; data aggregation; game theory; norms; reciprocation; self interested agents; simulation

Non-perturbing cavitation detection / monitoring in sonochemical reactors - Bornmann, Peter; Hemsel, Tobias; Sextro, Walter; Maeda, Takafumi; Morita, Takeshi (Ultrasonics Symposium (IUS), 2012 IEEE International)
To optimize the ultrasound irradiation for cavitation based ultrasound applications like sonochemistry or ultrasound cleaning, the correlation between cavitation intensity and the resulting effect on the process is of interest. Furthermore, changing conditions like temperature and pressure result in varying acoustic properties of the liquid. That might necessitate an adaption of the ultrasound irradiation. To detect such changes during operation, process monitoring is desired. Labor intensive processes, that might be carried out for several hours, also require process monitoring to increase their reliability by detection of changes or malfunctions during operation. In some applications cavitation detection and monitoring can be achieved by the application of sensors in the sound field. Though the application of sensors is possible, this necessitates modifications on the system and the sensor might disturb the sound field. In other applications harsh, process conditions prohibit the application of sensors in the sound field. Therefore alternative techniques for cavitation detection and monitoring are desired. The applicability of an external microphone and a self-sensing ultrasound transducer for cavitation detection were experimentally investigated. Both methods were found to be suitable and easily applicable.
Keywords: cavitation; chemical reactors; microphones; process monitoring; reliability; ultrasonic applications; ultrasonic waves; acoustic properties; cavitation based ultrasound applications; cavitation intensity; change detection reliability; external microphone; malfunction detection reliability; nonperturbing cavitation detection; nonperturbing cavitation monitoring; process monitoring; self-sensing ultrasound transducer; sonochemical reactors; sonochemistry; ultrasound cleaning; ultrasound irradiation; Acoustics; Liquids; Monitoring; Sensors; Sonar equipment; Transducers; Ultrasonic imaging

A hierarchical approach to unsupervised shape calibration of microphone array networks - Hennecke, Marius; Ploetz, Thomas; Fink, Gernot A.; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (IEEE/SP 15th Workshop on Statistical Signal Processing (SSP 2009))
Microphone arrays represent the basis for many challenging acoustic sensing tasks. The accuracy of techniques like beamforming directly depends on a precise knowledge of the relative positions of the sensors used. Unfortunately, for certain use cases manually measuring the geometry of an array is not feasible due to practical constraints. In this paper we present an approach to unsupervised shape calibration of microphone array networks. We developed a hierarchical procedure that first performs local shape calibration based on coherence analysis and then employs SRP-PHAT in a network calibration method. Practical experiments demonstrate the effectiveness of our approach especially for highly reverberant acoustic environments.
Keywords: acoustic sensing tasks; array geometry; calibration; coherence analysis; hierarchical procedure; local shape calibration; microphone array networks; microphone arrays; network calibration method; sensor arrays; SRP-PHAT; unsupervised shape calibration